Plasma Pro‐Endothelin‐1 Peptide Concentrations Rise in Chronic Kidney Disease and Following Selective Endothelin A Receptor Antagonism. Issue 3 (March 2015) - Dhaun, Neeraj; Yuzugulen, Jale; Kimmitt, Robert A.; Wood, Elizabeth G.; Chariyavilaskul, Pajaree; MacIntyre, Iain M.; Goddard, Jane; Webb, David J.; Corder, Roger
Abstract : Background: Endothelin 1 (ET‐1) contributes to chronic kidney disease (CKD) development and progression, and endothelin receptor antagonists are being investigated as a novel therapy for CKD. The proET‐1 peptides, endothelin‐like domain peptide (ELDP) and C‐terminal pro‐ET‐1 (CT‐proET‐1), are both potential biomarkers of CKD and response to therapy with endothelin antagonists. Methods and Results: We assessed plasma and urine ELDP and plasma CT‐proET‐1 in CKD patients with minimal comorbidity. Next, in a randomized double‐blind crossover study of 27 subjects with proteinuric CKD, we examined the effects of 6 weeks of treatment with placebo, sitaxentan (endothelin A antagonist), and nifedipine on these peptides alongside the primary end points of proteinuria, blood pressure, and arterial stiffness. Plasma ELDP and CT‐proET‐1 increased with CKD stage (both P <0.0001), correlating inversely with estimated glomerular filtration rate (both P <0.0001). Following intervention, placebo and nifedipine did not affect plasma and urine ELDP or plasma CT‐proET‐1. Sitaxentan increased both plasma ELDP and CT‐proET‐1 (baseline versus week 6±SEM: ELDP, 11.8±0.5 versus 13.4±0.6 fmol/mL; CT‐proET‐1, 20.5±1.2 versus 23.3±1.5 fmol/mL; both P <0.0001). Plasma ET‐1 was unaffected by any treatment. Following sitaxentan, plasma ELDP and CT‐proET‐1 correlated negatively with 24‐hour urinary sodium excretion. Conclusions: ELDP and CT‐proET‐1 increase in CKD and thus are potentially useful biomarkers of renal injury. Increases in response to endothelin A antagonism may reflect EDN1 upregulation, which may partly explain fluid retention with these agents. Clinical Trial Registration: URL:www.clinicalTrials.gov Unique identifier: NCT00810732